ChemInform Abstract: Convenient Synthesis of 2, 4‐Disubstituted Pyrido[2, 3‐d]pyrimidines via Regioselective Palladium‐Catalyzed Reactions. Issue 12 (14th March 2013) - Riadi, Yassine; Massip, Stephane; Leger, Jean‐Michel; Jarry, Christian; Lazar, Said; Guillaumet, Gerald
Abstract A novel and efficient route for the synthesis of the rare title compounds (V) is reported by sequential coupling involving a regioselective chlorine discrimination.